2014
DOI: 10.1002/2013jc009305
|View full text |Cite
|
Sign up to set email alerts
|

Study of the phytoplankton plume dynamics off the Crozet Islands (Southern Ocean): A geochemical-physical coupled approach

Abstract: The Crozet Archipelago, in the Indian sector of the Southern Ocean, constitutes one of the few physical barriers to the Antarctic Circumpolar Current. Interaction of the currents with the sediments deposited on the margins of these islands contributes to the supply of chemical elements-including iron and other micro-nutrients-to offshore high-nutrient, low-chlorophyll (HNLC) waters. This natural fertilization sustains a phytoplankton bloom that was studied in the framework of the KEOPS-2 project. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…The radium activities reported in this study are shown in Table 1 and fall in the range of previous radium data reported for surface waters near islands of the Southern Ocean (Annett et al, 2013;Charette et al, 2007;Dulaiova et al, 2009;Hanfland, 2002;Kaufman et al, 1973;Sanial et al, 2014;van Beek et al, 2008). The highest 223 Ra, 224 Ra and 228 Ra activities are found in seawater samples collected at shallow stations near the Kerguelen Islands (bathymetry < 200 m; Fig.…”
Section: Radium Distribution In Surface Waterssupporting
confidence: 84%
See 2 more Smart Citations
“…The radium activities reported in this study are shown in Table 1 and fall in the range of previous radium data reported for surface waters near islands of the Southern Ocean (Annett et al, 2013;Charette et al, 2007;Dulaiova et al, 2009;Hanfland, 2002;Kaufman et al, 1973;Sanial et al, 2014;van Beek et al, 2008). The highest 223 Ra, 224 Ra and 228 Ra activities are found in seawater samples collected at shallow stations near the Kerguelen Islands (bathymetry < 200 m; Fig.…”
Section: Radium Distribution In Surface Waterssupporting
confidence: 84%
“…The KEOPS-2 cruise was conducted during austral spring 2011 to the east of the Kerguelen Islands. Natural radio-tracers such as radium isotopes ( 223 Ra, T 1/2 = 11.4 d; 224 Ra, T 1/2 = 3.66 d; 228 Ra, T 1/2 = 5.75 yr) have already been proved to be powerful tools to track the origin and fate of chemical elements -including iron and other micronutrients -which are released by the sediments deposited on the shelves (Annett et al, 2013;van Beek et al, 2008;Charette et al, 2007;Dulaiova et al, 2009;Sanial et al, 2014). In this work, we refer to these latter inputs as "sediment-derived inputs".…”
Section: Sanial Et Al: Use Of Ra Isotopes To Deduce Rapid Transfementioning
confidence: 99%
See 1 more Smart Citation
“…In order to estimate iron delivery due to horizontal stirring, we use an advection scheme based on altimetry, extending to the Southern Ocean a Lagrangian model used for predicting the development of the Kerguelen phytoplanktonic plume . The model has been extensively calibrated and validated in the Crozet and Kerguelen regions by integrating satellite data (altimetry and ocean color), lithogenic isotopes, iron measurements, and drifters Sanial et al, 2014Sanial et al, , 2015. model seeds each open ocean location with a particle and finds the particle's most recent contact with a shallow bathymetry by a back trajectory issued from altimetry data.…”
Section: Lagrangian Modeling Of Horizontal Iron Fluxesmentioning
confidence: 99%
“…In support of this hypothesis, in-situ iron measurements from the Atlantic, North Pacific and Tasman Sea reveal high concentrations of iron on the pole-ward edge of the western boundary current extensions, corresponding to the Brazil Current, North Atlantic Current, Kuroshio Current and the East Australia Current (Lam et al, 2006;Nishioka et al, 2007Nishioka et al, , 2011Bowie et al, 2009;Rijkenberg et al, 2014;Schlosser et al, in preparation). Similarly, large fluxes of iron downstream of the Kerguelen and Crozet Islands have been attributed to the lateral advection of shelf sediment iron by ocean fronts (Blain et al, 2007(Blain et al, , 2008Planquette et al, 2007;Chever et al, 2010;Sanial et al, 2014;Van der Merwe et al, 2015). The source of this iron is thought to be from sediment re-suspension as fronts traverse continental and island shelves, as well as continentally weathered material entering coastal regions through surface runoff .…”
Section: The Role Of Ocean Fronts In Iron Supply To the Southern Oceanmentioning
confidence: 99%